Effects of nitrogen fertilizer basal-to-top-dressing ratios on maize straw decomposition, soil carbon and nitrogen, and bacterial community structure in different soil textures on the north china plain - Li, Jingyu; Yang, Xiaonan; Hou, Rui; Ma, Yujie; Wang, Yanqun; Ma, Yang; Zhen, Wenchao; Huang, Yuanyuan; Fu, Xin; Peng, Zhengping; Men, Mingxin (Frontiers in Microbiology, 2025)
Straw return is a recognized agricultural practice that improves soil quality, reduces reliance on chemical fertilizers, and supports sustainable agriculture. Its effectiveness is influenced by microbial changes under varying soil properties and fertilization practices. In a wheat–maize rotation system, field experiments were conducted over 2 years in loam and clay loam soils with five fertilizer (N) application treatments (i.e., no N fertilizer (N0) and N fertilizer basal-to-top-dressing ratios of 3:7 (N3:7), 4:6 (N4:6), 5:5 (N5:5), and 6:4 (N6:4)) to investigate the dynamics of maize straw decomposition, changes in soil organic carbon (SOC) and total nitrogen (TN) concentrations, soil bacterial diversity and abundance, and their interactions. Our results showed that the optimization of N fertilizer basal-to-top-dressing ratios enhanced SOC and TN by accelerating maize straw decomposition and nutrient release, as well as increasing plant carbon and nitrogen inputs. At the wheat maturity stage, the decomposition rate of maize straw reached 69.48–75.04%. The N4:6 and N5:5 ratios exhibited higher decomposition rates and C and N release rates in both soil textures. Compared to N0, N application treatments increased SOC and TN concentrations by 7.90–14.17% and 7.94–33.60%, respectively. The effects were most pronounced with the N4:6 ratio in loam and the N5:5 ratio in clay loam. Both soil textures had the same dominant bacterial phyla, but species abundance differed significantly. Loam had a significantly higher relative abundance of Proteobacteria and lower relative abundances of Gemmatimonadetes, Actinobacteria, and Chloroflexi than clay loam. N application significantly influenced bacterial diversity, with higher diversity observed with the N4:6 ratio in loam and the N5:5 ratio in clay loam. Structural equation modeling indicated that different N application treatments in loam influenced maize straw decomposition by altering the soil C/N ratio and bacterial community diversity, while in clay loam, N application treatments influenced maize straw decomposition mainly by altering the soil C/N ratio. Overall, the N4:6 treatment in loam and the N5:5 treatment in clay loam accelerated the decomposition and nutrient release of maize straw, enhanced SOC, TN, and bacterial community abundance, and provided a scientific basis for efficient straw utilization and sustainable agricultural development in the North China Plain region.